Influence of Dapagliflozin on Glycemic Variations in Patients with Newly Diagnosed Type 2 Diabetes Mellitus - Feng-fei Li; Gu Gao; Qian Li; Hong-hong Zhu; Xiao-fei Su; Jin-dan Wu; Lei Ye; Jian-hua Ma (Journal of Diabetes Research)
Objectives. To observe changes in blood glycemic variations and oxidative stress level before and after dapagliflozin treatment in patients with newly diagnosed T2DM. Methods. This was a randomized, double-blind, placebo-controlled, phase 3 trial. A total of 28 patients with newly diagnosed T2DM with HbA1c levels of 7.5–10.5% were randomly selected to receive dapagliflozin or placebo treatment for 24 weeks. After baseline data were collected, we analyzed glycemic variations and plasma 8-iso PGF2α level at baseline and at the endpoint. Primary outcome was the changes of mean amplitude glycemic excursion (MAGE) within groups. Results. After 24-week dapagliflozin therapy, our data showed the significant improvement of MAGE with dapagliflozin therapy (P=0.010). Compared with control group, patients in dapagliflozin group exhibited reduction in 24-hour MBG (P=0.026) and lower mean plasma glucose concentrations, especially during periods from 2400 to 0200 and 1300 to 1800 (P<0.05, resp.). In addition, plasma 8-iso PGF2α level was notably decreased in the treatment group compared to the control group (P=0.034). Conclusions. In conclusion, this study shows the ability of dapagliflozin to improve glycemic variations and associate with reduction of oxidative stress in patients with T2DM, which may benefit the cardiovascular system.